Value engineering in developing countries - Eusuf, Muhammad Abu; Mansour, Abeer Khalid (2015)
Conservation in Civil Engineering Construction is a familiar phenomenon, so most of the Civil Engineers prefer to reduce the unnecessary cost whenever possible without affecting the system. To achieve this, value engineering is the most economical and penetrating tool. Value engineering is a philosophy implemented by the use of a specific set of techniques, a body of knowledge and a group of learned skills; it is an organized creative approach of identification of unnecessary cost.